204k views
3 votes
(6x² - x+1) - (-4+ 2x² + 8x)

a. 8x² + 7x + 5
b. 8x² + 7x - 3
c. 4x² – 9x + 5
d. 4x² + 9x + 5​

User Bobby S
by
5.6k points

2 Answers

4 votes

Answer:

[C] 4x² − 9x + 5

Step-by-step explanation:

6x² − x + 1 − (−4 + 2x² + 8x)

[ Distribute the Negative Sign ]

= 6x² − x + 1 + −1(−4 + 2x² + 8x)

= 6x² + −x + 1 + (−1)(−4) + −1(2x²) + −1(8x)

= 6x² + −x + 1 + 4 + −2x² + −8x

[ Combine Like Terms ]

= 6x²2 + −x + 1 + 4 + −2x² + −8x

= (6x² + −2x²) + (−x + −8x) + (1 + 4)

= 4x² + −9x + 5

User Erdnase
by
5.4k points
4 votes

Answer:

Step-by-step explanation:

6x^2 - x + 1 + 4 - 2x^2 - 8x

4x^2 - 9x + 5

answer is C

User Bernhardw
by
5.2k points